Origin of personalized medicine in pioneering, passionate, genomic research - Barrera Saldaña, Hugo Alberto (2020)
Personalized medicine, one of the main promises of the Human Genome Project (HGP) that began three decades ago, is now a new therapeutic paradigm. With its arrival the era of developing drugs to suit all patients, yet often having to withdraw a promising new one because a minority of patients was at risk, even though it had proved valuable for the majority was consigned to history as were trial-and-error strategies being the predominant means of tailoring therapy. But how did it originate and the earliest examples emerge? Is it true that the first personalized diagnostic test was the companion test for Herceptin®? This account of a remarkable journey from genomic and translational research to therapeutic and diagnostic innovations, describes how sequencing the human growth hormone (hGH) locus provided proof of principle for HGP-inspired personalized medicine. Sequencing this locus and the resultant biomanufacture of HGH and the development of a test capable of detecting which patients would benefit from its administration helped silence the skeptics who questioned the validity of such an approach. The associated companion diagnostic was created four years before the invention of the HercepTest® (registered as the first companion diagnostics ever developed). By cultivating genomic research with passion and pursuing its applications, we and many others contributed to the emergence of a new diagnostics industry, the discovery of better actionable gene-targets and to a revitalized pharmaceutical industry capable of developing safer and more effective therapies. In combination, these developments are beginning to fulfill the promise of the HGP, offering each patient the opportunity to adopt the right treatment at the correct dosage in an opportune manner.